2018
DOI: 10.1159/000487938
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Rapid Cognitive Decline in Patients with Mild-to-Moderate Alzheimer Disease: A Prospective Cohort Study with 12-Month Follow-Up Performed in Memory Clinics

Abstract: Background/Aims: Alzheimer disease (AD) is particularly devastating, with no cure, no means of prevention, and no proven way to slow progression. AD is associated with the worsening of cognitive function attributable to a variety of factors of which little is known. Our main objective was to determine factors associated with rapid cognitive decline (RCD) in older AD patients. Methods: We conducted a 12-month, prospective, multi-centre cohort study. Community-living individuals aged ≥65 years with mild-to-moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
2
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 42 publications
4
31
2
10
Order By: Relevance
“…One study in rural areas of northern China indicates that risk factors for cognitive deficits were female sex, low education, and central obesity . Moreover, another study shows that female sex and lower education were associated with vascular cognitive impairment (VCI) in Chinese stroke patients TA B L E 4 Linear regression between 3-month MMSE scores and variables of stroke patients, adjusted R 2 = 0.416 (Mellon et al, 2015;Pendlebury, 2009;Tchalla et al, 2018), which is consistent with our results. In addition, among older AD patients with rapid cognitive decline (RCD), females had significantly lower MMSE scores after adjusting for other variables (Chen et al, 2016).…”
Section: Tions Can Inhibit Both Aβ Deposition and Tau Hyperphosphorylsupporting
confidence: 89%
See 1 more Smart Citation
“…One study in rural areas of northern China indicates that risk factors for cognitive deficits were female sex, low education, and central obesity . Moreover, another study shows that female sex and lower education were associated with vascular cognitive impairment (VCI) in Chinese stroke patients TA B L E 4 Linear regression between 3-month MMSE scores and variables of stroke patients, adjusted R 2 = 0.416 (Mellon et al, 2015;Pendlebury, 2009;Tchalla et al, 2018), which is consistent with our results. In addition, among older AD patients with rapid cognitive decline (RCD), females had significantly lower MMSE scores after adjusting for other variables (Chen et al, 2016).…”
Section: Tions Can Inhibit Both Aβ Deposition and Tau Hyperphosphorylsupporting
confidence: 89%
“…In addition, among older AD patients with rapid cognitive decline (RCD), females had significantly lower MMSE scores after adjusting for other variables (Chen et al, 2016). Moreover, another study shows that female sex and lower education were associated with vascular cognitive impairment (VCI) in Chinese stroke patients TA B L E 4 Linear regression between 3-month MMSE scores and variables of stroke patients, adjusted R 2 = 0.416 (Mellon et al, 2015;Pendlebury, 2009;Tchalla et al, 2018), which is consistent with our results. In China, females prefer not to exercise outdoors and always stay away from ultraviolet light (UV), which leads to lower serum vitamin D (Vit D) levels (Montagne et al, 2018;Wang, Zhu, Liu, Tu, & He, 2018).…”
Section: Ta B L E 3 Relevance Between 3-month Mmse Scores and Baselinsupporting
confidence: 87%
“…In Table 2 are given the predictive factors of poorer outcomes in AD found in the different papers revised. Among demographic variables, there are four predictors that appeared consistently across many cohort studies: male gender [15][16][17][18][19][20][21][22][23] and extrapyramidal signs [24][25][26][27][28][29], which are associated with both shorter survival and faster cognitive decline. Only in one study the female gender was associated with poorer outcome [30].…”
Section: Demographic Factorsmentioning
confidence: 99%
“…13. Signs of parkinsonism [26][27][28][29]43,61] 14. Nutritional status [30,74] Determinants of Progression and Mortality in Alzheimer's disease: A Systematic Review the HR did not reach statistical significance (HR: 1.22) [22].…”
mentioning
confidence: 99%
“…Among them, malnutrition was recognized as a risk factor of dementia and AD [6,7]. Recent evidence suggests that malnutrition is associated with rapid cognitive decline, disease progression and the degree of impairment in daily functioning in patients with dementia [8][9][10]. While studies have shown that patients with dementia or AD were more likely to suffer from a poor nutritional status [11,12].…”
Section: Introductionmentioning
confidence: 99%